E-Commerce Strategies and Customer Experience as Drivers of Purchase Intention: A Case Study of Maju Bersama Supermarket, Medan City - Dina Antika Pohan; Dwi Fany Fransiska Dewi Butar-Butar; Siti Junaida Hasibuan (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This study investigates the influence of e-commerce implementation and customer experience on purchase intention at Maju Bersama Supermarket in Medan City, Indonesia. The research aims to determine the extent to which these variables, both individually and collectively, affect consumer purchase intentions in a hybrid retail environment Materials and methods: A quantitative research approach was employed using accidental sampling technique. The study population consisted of 1,252 registered members of Maju Bersama Supermarket, with a sample size of 93 respondents calculated using the Slovin formula with a 10% margin of error. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis with SPSS version 22. Validity and reliability tests were conducted, followed by classical assumption tests (normality, multicollinearity, and heteroscedasticity) before hypothesis testing. Results: The regression equation Y = 10.151 + 0.176X₁ + 0.395X₂ indicates that both e-commerce (X₁) and customer experience (X₂) positively influence purchase intention. Partial hypothesis testing revealed that e-commerce significantly affects purchase intention (t = 3.476 > t-table = 1.662, p = 0.001), as does customer experience (t = 4.432 > t-table = 1.662, p < 0.001). Simultaneous testing confirmed that both variables collectively influence purchase intention (F = 15.628 > F-table = 3.098, p < 0.001). The adjusted R² value of 0.241 (24.1%) suggests that these variables explain approximately one-quarter of the variance in purchase intention, with the remaining 75.9% attributable to other factors not examined in this study. Conclusions: E-commerce implementation and customer experience are significant predictors of purchase intention in the retail supermarket context. Customer experience demonstrates a stronger influence (β = 0.403) compared to e-commerce (β = 0.316), suggesting that while digital platforms facilitate commerce, the quality of customer interactions remains paramount. Retailers should prioritize both technological infrastructure development and experiential service quality to maximize purchase intentions. Future research should explore additional variables within the unexplained 75.9% variance, such as price perception, product quality, brand trust, and competitive positioning.